ANALIS PENGUKURAN KINERJA RSUD DR. PIRNGADI DENGAN METODE BALANCE SCORECARD - Rahmah Abidah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
Each Public Health Unit used to measure its performance in order to improve services to customers, employees, communities, and stakeholders. The next step is the development of a performance measurement system using the Balanced Scorecard approach to develop the hospital in achieving its strategic vision and mission goals. Performance indicators are identified and adjusted according to the availability of information that has been collected through the interviewees. The purpose of this study was to determine the implementation of the Balance Score Card regarding the performance measurement system in the Public Health Unit. In this study, 25 questionnaires were sent to health services at RSUD Dr. Pinardi.